Interpretasi Lam Nahy dalam Tafsir Ath-Thabari - Syayfi, Sohib; Aulia, Dini (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2022)
The key to the success and prosperity of a person's life in this world and in the hereafter is piety and noble character. Unfortunately, immoral and disgraceful behavior is increasingly widespread in this day and age. For example, there are many cases of bullying, humiliation, cyberbullying, usury transactions, the behavior of associating partners with Allah, hedonism and others. The purpose of this study is to find out what is the relationship between the commandment of piety and lam nahy in the Qur'an according to Ath-Tabari's interpretation. The method used in this research is thematic method. The result of this study is that piety is mostly interpreted by staying away from things that are prohibited. Among the prohibitions that accompany the commandment of piety are the prohibition of division, usury transactions, committing shirk and kufr, being negligent, turning away from Islamic law, committing sukhriyyah, tajassus, prejudice and backbiting. Thus all the prohibited verses have a very close relationship with the commandment of piety. Because breaking the prohibition will weaken, reduce, and even damage the perfection of faith. In addition, the command of piety will not be perfect except by staying away from and leaving all His prohibitions.